Baseline Obesity Status Modifies Effectiveness of Adapted Diabetes Prevention Program Lifestyle Interventions for Weight Management in Primary Care. (4th December 2013) - Azar, Kristen M. J.; Xiao, Lan; Ma, Jun
Abstract : Objective . To examine whether baseline obesity severity modifies the effects of two different, primary care-based, technology-enhanced lifestyle interventions among overweight or obese adults with prediabetes and/or metabolic syndrome. Patients and Methods . We compared mean differences in changes from baseline to 15 months in clinical measures of general and central obesity among participants randomized to usual care alone (n = 81 ) or usual care plus a coach-led group (n = 79 ) or self-directed individual (n = 81 ) intervention, stratified by baseline body mass index (BMI) category. Results . Participants with baseline BMI 35 + had greater reductions in mean BMI, body weight (as percentage change), and waist circumference in the coach-led group intervention, compared to usual care and the self-directed individual intervention (P < 0 . 05 for all). In contrast, the self-directed intervention was more effective than usual care only among participants with baseline BMIs between 25 ≤ 35 . Mean weight loss exceeded 5% in the coach-led intervention regardless of baseline BMI category, but this was achieved only among self-directed intervention participants with baseline BMIs < 35 . Conclusions . Baseline BMI may influence behavioral weight-loss treatment effectiveness. Researchers and clinicians should take an individual's baseline BMI into account when developing or recommending lifestyle focused treatment strategy. This trial is registered with ClinicalTrials.gov NCT00842426 .